Reproductive programs for beef cattle: incorporating management and reproductive techniques for better fertility - Vasconcelos, Jose Luiz M. [UNESP]; Carvalho, Rafael [UNESP]; Peres, Rogerio F. G. [UNESP]; Rodrigues, Adnan D. P. [UNESP]; Claro Junior, Izaias [UNESP]; Meneghetti, Mauro [UNESP]; Aono, Fernando H. [UNESP]; Costa, Wedson M. [UNESP]; Lopes, Catarina N. [UNESP]; Cooke, Reinaldo F.; Pohler, Ky G. (Brazilian Coll Animal Reproduction, 2017)
This review summarizes strategies to increase overall pregnancy rates to TAI protocols, and potential areas for improvement in reproductive management of Nelore cows. Low BCS at calving and postpartum BCS loss negatively impacted percentage of pregnant females to TAI, with primiparous cows being the most sensitive to the effects of low BCS during the postpartum period. The current reproductive management recommended for replacement heifers (with TAI on day 0) consist of intravaginal progesterone device insertion from day -35 to -23, 0.6 mg i.m. injection of estradiol cypionate on day -23, insertion of another intravaginal progesterone device and 2.0 mg i.m. injection of estradiol benzoate on day -11, 12.5 mg i.m. injection of dinoprost tromethamine on day -4, intravaginal progesterone device removal and 0.6 mg i.m. injection of estradiol cypionate on day -2, and TAI on day 0. Supplementing corn for 41 days after the first TAI of the breeding season increased pregnancy to a second AI in primiparous cows, increased final proportion of pregnancy in primiparous cows, but decreased the final proportion of pregnancy in mature cows. In turn, supplementing melengestrol acetate or Ca salts of PUFA during the expected time of luteolysis was beneficial to pregnancy rates. Vaccinating cows against BoHV-1, BVDV, and Leptospira spp., particularly when both doses were administered before TAI, improved cow reproductive performance. Cow temperament has direct implications not only on reproductive efficiency of B. indicus females, but also on overall production efficiency in cow-calf system based on B. indicus cattle. Lastly, concentration of pregnancy-associated glycoproteins was driven by the ability of pregnancy maintenance and by sire used at TAI, whereas exploring this relationship might be interesting to improve sire fertility regarding late embryonic loss in Nelore females.
Keywords: beef females; puberty; timed artificial insemination; Nelore; management strategies; reproduction